Reassembling and remembering - the politics of reconciliation in South Africa - J. Kruger (Acta Theologica)
This article proposes that the work of the French sociologist of science, Bruno Latour, that conceptualises the political process in a highly pluralist society, can provide a useful starting point for a discussion on the politics of reconciliation. It is especially Latour’s suggestion of an object-oriented politics that will be explored and applied to the South African situation. Subsequently, however, it is argued that Latour’s politics of “reassembling” should be complemented by a politics of remembering. The latter notion is understood in a Platonic-Augustinian fashion – following the interpretation of the contemporary philosophical-theological movement of Radical Orthodoxy – as a diffuse recognition of the other within the self, whereby the politics of reconciliation is, in an important sense, broadened to encompass the interior, psychic and, ultimately, spiritual aspects of the relation between the self and the other. The paper concludes with some remarks on the role of the church as the narrative embodiment of reconciliation conceived as reassembling ánd remembering.